Rural windfall or a new resource curse? coca, income, and civil conflict in Colombia - Joshua D. Angrist; Adriana D. Kugler (Institute for the Study of Labor (IZA), 2007)
Natural and agricultural resources for which there is a substantial black market, such as coca, opium, and diamonds, appear especially likely to be exploited by the parties to a civil conflict. Even legally traded commodities such as oil and timber have been linked to civil war. On the other hand, these resources may also provide one of the few reliable sources of income in the countryside. In this paper, we study the economic and social consequences of a major exogenous shift in the production of one such resource coca paste into Colombia, where most coca leaf is now harvested. Our analysis shows that this shift generated only modest economic gains in rural areas, primarily in the form of increased self-employment earnings and increased labor supply by teenage boys. The results also suggest that the rural areas which saw accelerated coca production subsequently became more violent, while urban areas were affected little. The acceleration in violence is greater in departments (provinces) where there was a pre-coca guerilla presence. Taken together, these findings are consistent with the view that the Colombian civil conflict is fueled by the financial opportunities that coca provides, and that the consequent rent-seeking activity by combatants limits the economic gains from coca cultivation.
urn:nbn:de:101:1-20080401406
Keywords: 330; Koka; Ländliches Einkommen; Ländliche Entwicklung; Bürgerkrieg; Kolumbien